1995
DOI: 10.1104/pp.107.3.915
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Induced Accumulation of hsp90 Transcripts in Brassica napus

Abstract: Characterization of the expression of hsp90 genes of Brassica napus by northern blot analysis and immunoblotting showed that the hsp90 mRNA and protein are present in all B. napus tissues examined, albeit at different levels. High levels of hsp90 mRNA and protein were found in young and rapidly dividing tissues such as shoot apices and flower buds, suggesting that hsp90 may have an important role in plant growth and development. A significant increase in hsp90 mRNA levels was detected in seedlings exposed to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
2
8

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 36 publications
6
92
2
8
Order By: Relevance
“…Recently, Queitsch et al (2002) showed that HSP90 may act as a capacitor, as had been proposed previously in Drosophila (Rutherfort and Lindquist, 1998). Genes encoding HSP90, along with their pattern of expression at the mRNA level, have been reported in maize (Marrs et al, 1993), barley (Walther-Larsen et al, 1993), tomato (Koning et al, 1992), periwinkle (Schroder et al, 1993), Brassica (Krishna et al, 1995;Neumann et al, 1993;Reddy et al, 1998), Arabidopsis (Conner et al, 1990;Takahashi et al, 1992), Pharbitis (Felsheim and Das, 1992), and rye (Schmitz et al, 1996), but the functional signi®cance of their expression patterns is not clear. In Arabidopsis, there are at least six HSP90 genes in addition to CR88.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, Queitsch et al (2002) showed that HSP90 may act as a capacitor, as had been proposed previously in Drosophila (Rutherfort and Lindquist, 1998). Genes encoding HSP90, along with their pattern of expression at the mRNA level, have been reported in maize (Marrs et al, 1993), barley (Walther-Larsen et al, 1993), tomato (Koning et al, 1992), periwinkle (Schroder et al, 1993), Brassica (Krishna et al, 1995;Neumann et al, 1993;Reddy et al, 1998), Arabidopsis (Conner et al, 1990;Takahashi et al, 1992), Pharbitis (Felsheim and Das, 1992), and rye (Schmitz et al, 1996), but the functional signi®cance of their expression patterns is not clear. In Arabidopsis, there are at least six HSP90 genes in addition to CR88.…”
Section: Discussionmentioning
confidence: 83%
“…The proteins are localized in different cell compartments, including the cytoplasm, the endoplasmic reticulum, and chloroplasts (Koning et al, 1992;Takahashi et al, 1992;Marrs et al, 1993;Schrö der et al, 1993;Krishna et al, 1995;Schmitz et al, 1996;Milioni and Hatzopoulos, 1997). The corresponding genes were shown to be specifically expressed during embryogenesis, pollen development (Marrs et al, 1993), and seed germination (Reddy et al, 1998) in young and rapidly divid- Article, publication date, and citation information can be found at www.plantphysiol.org/cgi…”
mentioning
confidence: 99%
“…The proteins are localized in different cell compartments, including the cytoplasm, the endoplasmic reticulum, and chloroplasts (Koning et al, 1992;Takahashi et al, 1992;Marrs et al, 1993;Schrö der et al, 1993;Krishna et al, 1995;Schmitz et al, 1996;Milioni and Hatzopoulos, 1997). The corresponding genes were shown to be specifically expressed during embryogenesis, pollen development (Marrs et al, 1993), and seed germination (Reddy et al, 1998) in young and rapidly divid-ing tissues such as shoot and root apices (Koning et al, 1992) and in flowers (Takahashi et al, 1992;Krishna et al, 1995). In oilseed rape (Brassica napus) and tomato (Lycopersicon esculentum) seedlings, HSP90 protein levels were found to increase by exogenous 24-epibrassinolide application (Dhaubhadel et al, 1999), whereas a glucosinolate-deficient Arabidopsis mutant was shown to be thermosensitive and defective in the cytosolic HSP90 expression after heat stress (Ludwig-Muller et al, 2000).…”
mentioning
confidence: 99%
“…First, some heat-shock inducible genes in rice and Brassica napus such as low-molecularmass HSP (Wang et al 2015), high-molecular-mass HSPs (Krishna et al 1995, Pareek et al 1995, and ascorbate peroxidase (Sato et al 2001) are upregulated under cold stress. Secondly, heat shock factors function as H2O2 sensors (Miller and Mittler 2006) and heat shock responsive genes have been implicated in ROS equilibrium (Davletova et al 2005, Kumar et al 2012.…”
Section: Utilization Of Hsfs For Enhancing Cold Stress Tolerancementioning
confidence: 99%